Problematika Penegakan Qanun Jinayat di Aceh - M. Arif Fadillah A. Tanjung; Firmansyah Firmansyah; Fauziah Lubis (Fakultas Syariah IAIN Laa Roiba Bogor, 2024)
After the enactment of Qanun No. 6 Year 2014 on (Qanun Jinayat), several problems arose, both internal and external. After the enactment of Qanun No. 6 of 2014 on (Qanun Jinayat), several problems arose, both internal and external problems. Internal problems arise with a variety of problems, facilities and infrastructure are not yet complete, the emergence of polemics about the place of execution of flogging, socialization is still considered insufficient, uneven resolution of Qanun Jinayah enforcement problems in each district / city, the emergence of differences in interpretation in Jinayat cases resolved by Jinayat law and Qanun fostering customary law, between one gampong and another gampong differ in the type of customary sanctions on khalwat, varied in the type of sanctions and law enforcement. More specifically, the internal problems faced in the implementation of Qanun Jinayat in Aceh are from the law enforcement apparatus itself (Wilayatul Hisbah, Police, Attorney General's Office, and Syar`iyah Court) and traditional leaders who have different perceptions of Qanun Jinayat. This not only leads to variations in application, but also often obscures the legal certainty desired by a regulation. The author conducts this research using empirical juridical research method which is a legal research method that uses empirical facts taken directly from the object of research in this case including the Community, University, and Islamic Shari'at Office of Aceh Province either by conducting interviews or direct observation. and with conceptual and statutory approaches using normative juridical methods. The data source used is data obtained indirectly through literature study. The legal materials obtained are then analyzed using descriptive-qualitative analysis to obtain conclusions that can be scientifically accounted for.